2020
DOI: 10.3390/agronomy10121848
|View full text |Cite
|
Sign up to set email alerts
|

Linking Cover Crop Residue Quality and Tillage System to CO2-C Emission, Soil C and N Stocks and Crop Yield Based on a Long-Term Experiment

Abstract: Cover crops (CC), particularly legumes, are key to promote soil carbon (C) sequestration in no-tillage. Nevertheless, the mechanisms regulating this process need further elucidation within a broad comprehensive framework. Therefore, we investigated effects of CC quality: black oat (Avena strigosa Schreb) (oat), common vetch (Vicia sativa L.) (vetch), and oat + vetch on carbon dioxide-C (CO2-C) emission (124 days) under conventional- (CT), minimum- (MT) and no-tillage (NT) plots from a long-term experiment in S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 106 publications
0
7
0
Order By: Relevance
“…These results emphasize the importance of using cover crop species with deep root systems to increase the C recovery in both the topsoil layer (0–0.15 m) and the soil profile (0–1.0 m). The deep and continuous biopores could connect the shallow layer and deep layer, supporting C translocation through the soil profile (Chabbi et al, 2009; Leal et al, 2020; Nicoloso et al, 2018; Rumpel & Kogel‐Knabner, 2011). The increase of C storage at depth is related to the high precipitation, soil structure, and well‐drained Oxisol characteristics that allow deep root growth and continuous dissolved C movement into the soil profile (Nicoloso et al, 2018; Rumpel & Kogel‐Knabner, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results emphasize the importance of using cover crop species with deep root systems to increase the C recovery in both the topsoil layer (0–0.15 m) and the soil profile (0–1.0 m). The deep and continuous biopores could connect the shallow layer and deep layer, supporting C translocation through the soil profile (Chabbi et al, 2009; Leal et al, 2020; Nicoloso et al, 2018; Rumpel & Kogel‐Knabner, 2011). The increase of C storage at depth is related to the high precipitation, soil structure, and well‐drained Oxisol characteristics that allow deep root growth and continuous dissolved C movement into the soil profile (Nicoloso et al, 2018; Rumpel & Kogel‐Knabner, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of maize in the summer crop rotation with soybean is another strategy to increase SOC (Amado et al, 2006; Campos et al, 2011; Sisti et al, 2004); De Oliveira Ferreira et al, 2012; Leal et al, 2020). These authors observed that maize, following a leguminous cover crop, increases the biomass input resulting in the increase of SOC.…”
Section: Discussionmentioning
confidence: 99%
“…A business-as-usual attitude towards agricultural production in most world regions will fail to deliver sustainable production intensification to meet future needs [1,2]. Therefore, there is an urgent need for the redesign of agriculture production systems in order to decrease environmental, economic, and social costs associated with current intensive tillage-based production systems that create bare soils and entail high agrochemical applications [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the positive results obtained, it has been gradually spreading worldwide to address important shortcomings of 'businessas-usual' tillage agriculture in addressing societal needs and environmental challenges. The three interlinked principles that define CA are: (a) continuously minimizing or avoiding mechanical soil disturbance by tillage of all forms, including no inversion of soil layers, and reducing the rate of crop residue break down and avoiding mixing it into the soil, thus preventing short-term peaks of biological activity associated with flushes of carbon (C) and nitrogen (N) soil inputs and the disruption of soil physical aggregates; (b) maintaining year-round diverse vegetative biomass mulch cover with living and dead plant material over the soil to protect the soil surface and serve as a continuous and diversified source of substrate for a diverse community of soil microorganisms; and (c) enhancing plant species diversification in the cropping system through crop rotations and associations, including cover crops that would utilize any spare time windows between cash crops, including N-fixing legumes which result in a high quality crop biomass input into the soil, enhancing plant-growth promoting bacteria and fungi [1,3,6,7]. Currently, Brazil has about 43 M ha under CA cropland of varying time durations spread across different agro-ecoregions reflecting the continental dimensions of the country (i.e., the fifth largest territorial country in the world in terms of area) and diverse farming traditions [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation